Multifaceted involvements of Paneth cells in various diseases within intestine and systemically - Cui, Chenbin; Wang, Xinru; Li, Lindeng; Wei, Hongkui; Peng, Jian (Frontiers in Immunology, 2023)
Serving as the guardians of small intestine, Paneth cells play an important role in intestinal homeostasis maintenance. Although Paneth cells uniquely exist in intestine under homeostasis, the dysfunction of Paneth cells is involved in various diseases not only in intestine but also in extraintestinal organs, highlighting the systemically importance of Paneth cells. The mechanisms under the participation of Paneth cells in these diseases are various as well. Involvements of Paneth cells are mostly characterized by limiting intestinal bacterial translocation in necrotizing enterocolitis, liver disease, acute pancreatitis and graft-vs-host disease. Risk genes in Paneth cells render intestine susceptible to Crohn’s disease. In intestinal infection, different pathogens induce varied responses in Paneth cells, and toll-like receptor ligands on bacterial surface trigger the degranulation of Paneth cells. Increased level of bile acid dramatically contributes to impairment of Paneth cells in obesity. Paneth cells display beneficial effects on the alleviation of COVID-19 via inhibition of virus entry and promotion of intestinal regeneration. On the contrary, abundant IL-17A in Paneth cells aggravates multi-organ injury in ischemia reperfusion. Pro-angiogenic effect of Paneth cells driven by microbial signals leads to the deterioration of portal hypertension. Therapeutic strategies targeting Paneth cells partly include improvement in Paneth cell function, inhibition of Paneth cell death, antibacterial peptide treatment and protection of intestinal stem cells. In this review, we discuss the influence and importance of Paneth cells in intestinal and extraintestinal diseases as reported so far, as well as the potential therapeutic strategies targeting Paneth cells.